Regulasi Ketenagakerjaan di Indonesia: Hak, Kewajiban, dan Tantangan - Arfan Pramanta Sadelanuari; Romi Faslah (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Labor regulation in Indonesia plays a crucial role in creating a harmonious industrial relationship between workers and employers. This article aims to examine the fundamental aspects of labor law, including the rights and obligations of both parties, types of employment agreements, as well as the challenges and recent developments in labor regulation. Using a descriptive-qualitative approach and literature review, the article concludes that despite several legal reforms—such as the implementation of the Job Creation Law—significant challenges remain, particularly concerning the protection of informal sector workers, outsourcing practices, and the dynamics of the digital labor market. An adaptive and participatory legal approach is needed to ensure a balance between labor market flexibility and the protection of workers' rights.